Red dot design concept yearbook. - Koo, Ken, ....- (Singapore : Red dot.)
The yearbooks, which present all prizewinning concepts, have gained an undisputed reputation as compilations of exceptional designs in the design scene. The books provide exciting behind-the-scenes insights, with detailed introductions of the jury members as well as product descriptions supplemented by portrayals of designers. The books summarise the main trends in concept design in an entertaining and informative fashion.